2011
DOI: 10.1002/ptr.3489
|View full text |Cite
|
Sign up to set email alerts
|

Fucoidan from Undaria pinnatifida Induces Apoptosis in A549 Human Lung Carcinoma Cells

Abstract: Fucoidan, a sulfated polysaccharide, has various biological activities, such as anticancer, antiangiogenic and antiinflammatory effects; however, the mechanisms of action of fucoidan on anticancer activity have not been fully elucidated. The anticancer effects of fucoidan from Undaria pinnatifida on A549 human lung carcinoma cells were examined. Treatment of A549 cells with fucoidan resulted in potent antiproliferative activity. Also, some typical apoptotic characteristics, such as chromatin condensation and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(62 citation statements)
references
References 34 publications
5
56
0
1
Order By: Relevance
“…Fucoidan (50 μg/mL) decreased LLC proliferation, migration, invasion, and survival capacities. These results are consistent with those of several previous studies, which showed that fucoidan inhibited cell viability and metastasis, and facilitated apoptosis in lung cancer cells [13][14][15][16] .…”
Section: Discussionsupporting
confidence: 95%
“…Fucoidan (50 μg/mL) decreased LLC proliferation, migration, invasion, and survival capacities. These results are consistent with those of several previous studies, which showed that fucoidan inhibited cell viability and metastasis, and facilitated apoptosis in lung cancer cells [13][14][15][16] .…”
Section: Discussionsupporting
confidence: 95%
“…Further, fucoidan has been indicated to play a role in apoptosis [28,35,36]. In one study, it induced the cleavage of PARP (poly ADP ribose polymerase) to the 89 kDa polypeptide, suggesting that caspases were involved in the fucoidan-mediated apoptosis [37]. Furthermore, in a study in rabbits investigated fucoidan injected intramuscular (i.m.…”
Section: Discussionmentioning
confidence: 99%
“…Fucoidan has been reported to inhibit the growth of a wide range of tumor cells [43,46]. It has also been shown to induce apoptosis in colon cancer HT-29 and HCT116 cells in a dose-dependent manner [15,49]. Kim et al .…”
Section: Seaweed and Colorectal Cancermentioning
confidence: 99%